Nilai-Nilai Kerukunan dalam Naskah Serat Waosan Puji - Zakiyah Zakiyah (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2012)
This paper discusses a manuscript entitled Serat Waosan Puji, a collection of the Widya Budaya Library of the Yogyakarta Kingdom. The manuscript which is in a good condition and readable consists of several texts. They tell about do’a (prayer), pillar of faith, pillar of Islam, theology, name of verses of al-Qur’an, Ki Purwadaksina’s teaching, Serat Nitisruti, and Serat Nitipraja. Meanwhile, the teaching of harmony is stated in three pupuh (chapters) dhandhanggula of Ki Purwadaksina’s teaching, Serat Nitisruti, and serat Nitipraja.